ANALISIS STRATEGI PEMASARAN DENGAN METODE SWOT DAN PERSPEKTIF SYARIAH PADA PT NATURAL NUSANTARA YOGYAKARTA - Mega Tunjung Hapsari (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2020)
Environmental and ecosystem damage globally has led PT Natural Nusantara to carry halal and environment friendly products in the field of agro-complex. However, fierce and fast business competition requires an appropriate marketing strategy in decision making. This study aims to analyze marketing strategies through the SWOT method and sharia perspective at PT Natural Nusantara Yogyakarta. The research method uses a descriptive qualitative approach based on primary and secondary data. The results of the study based on the Strengths - Weaknesses - Opportunities - Threats (SWOT) matrix, supported by the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Cartesius Diagram showed that the score of IFE 3,36 and EFE 3,20. This score indicates the quadrant I position, which is the strategy needed is growth oriented strategy. Besides that, business commitment based on virtue and piety in product marketing evidenced by the permission from BPOM and halal certification from MUI.